INCREMENTAL AND RADICAL INNOVATIONS IN MICRO AND SMALL ENTERPRISES: EVIDENCE FROM THE ALI PROGRAM IN PERNAMBUCO - Macedo, Marcos Roberto Gois de Oliveira (Seven Editora, 2026)
This article analyzes the impacts of technological and managerial innovations — classified as incremental or radical — on the productivity and survival capacity of micro and small enterprises (MSEs), based on the experience of the ALI (Local Innovation Agents) Program in Pernambuco, Brazil. Given the growing need for innovation strategies tailored to the profile of MSEs, an analytical model was proposed based on the adaptation of the Sectoral Innovation Degree (GIS), which led to the creation of the Incremental Innovation Degree (G²I). The study evaluated 48 companies using the Sebrae Innovation Radar, classifying 18 themes into technological and managerial axes according to their diffusion in the sector. The results show that approximately half of the indicators analyzed represent radical innovations, highlighting an untapped potential for disruptive practices. The G²I model proved to be a useful tool for diagnosing innovation maturity, guiding the prioritization of strategies, and supporting public innovation policies based on empirical and contextualized evidence.